Musculoskeletal Disorders in Clinical Dentistry and Their Prevention - Bhandari, Shikha Baghi; Bhandari, Rajat; Uppal, Ranjit Singh; Grover, Deepak (Journal of Orofacial Research, 2013)
In the dental profession, dental professionals spend their work days in an awkward, static position performing extremely precise procedures. Maintaining the steady hand and posture comes at a cost to the back, neck and shoulder area of the dental professional. Occasional pains from irregular stances or positions are to be expected while they are performing staticwork. However, when the pain becomes a regular occurrence, cumulative damage could arise leading to debilitating injuries. Work-related musculoskeletal disorders are a commoncomplaint of practicing dentists and dental hygienists. This article provides a brief review of literature on musculoskeletal disorders in clinical dentistry and various strategies of their prevention with a special emphasis on the neutral position for the clinicians and dental operators with an aim that it should help the dental operators to prevent these injuries and to work effectively and efficiently.